UI/UX Design Using Design Thinking Method Based on Website Unload Repair - Bonari, Anggiet Harjo Baskoro; Putra, Fajar Ariya (Universitas Trilogi, 2025)
Unload Repair is a PC repair service that can solve problems with computers or laptops. However, the current problem is that marketing through social media tends to be a little bit about information about service services, making it difficult for customers to receive the information. This study aims to create a User Interface (UI) and User Experience (UX) design that can make it easier for customers to see what services are provided by Unload Repair and help customers in ordering repair services using the Design Thinking method. Design Thinking is a method that involves users in every stage of design, starting from a deep understanding of their needs, to producing a prototype that can be tested to measure the effectiveness of the design. Design thinking includes the Empathize, Define, Ideate, Prototype and Testing stages. The Design Thinking method used is to create solutions based on problems in order to create designs that are easy to use and understand for users. The design was tested using Usability testing on 50 respondents, thus it was concluded that the UI/UX design on the Unload Repair website in the city of Jakarta can be used easily by users and has a positive experience based on the results of the respondents obtained and gets good satisfaction from Unload Repair website users.